Hubungan Stres Kerja Dengan Kinerja Bidan Dalam Masa Pandemik Covid-19 Di Kota Pontianak - Affi Zakiyya; Monika Natalia Pratiwi; Dianna (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Work stress on midwives during the COVID-19 pandemic can occurred due tohigh working hours, long working hours, mindset, limited number of health workerswhile the number of patients continued to grow and work safety procedures continueto change along with the development of the virus. If midwives did not manage workstress properly this will have an impact on their performance in providing healthservices to patients. To analyse the relationship between work stress and the midwifeperformance during pandemic covid-19 in Pontianak. Quantitative with cross sectionaldesign. The sample of this study was 43 midwives in Pontianak. Sampling with totalsampling method. The results of this study were 23 respondents (53.5%) whoexperienced work stress and 20 respondents (46.5%) who did not experience workstress. On the performance of midwives there were 25 respondents (58.1%) with good performance and 18 respondents (41.9%) with poor performance. Based on the Chisquare test, the p value = 0.004 meant that the sig value was smaller than(0.004 <0.05) indicating that work stress was related to the performance of midwivesduring the COVID-19 pandemic in Pontianak. Work stress was related to theperformance of midwives during the COVID-19 pandemic in Pontianak with a p value= 0.004.Keywords: Work Stress, Midwife Performance, COVID-19 Pandemic